How do you simplify #(12x^2+6x+90)/(6x^2-54)#?

1 Answer
Nov 10, 2016

Answer:

#=((2x^2 +x +15))/((x+3)(x-3)#

Explanation:

With algebraic fractions, always try to find factors first..

#(6(2x^2 +x +15))/(6(x^2 -9))" "larr# common factor of 6

#=(6(2x^2 +x +15))/(6(x+3)(x-3)#

#=((2x^2 +x +15))/((x+3)(x-3)#

This does not simplify further.
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

However, if the numerator had been #12x^2+6x-90#

We would have:

#(6(2x^2 +x -15))/(6(x^2 -9)#

#=(6(2x-5)(x+3))/(6(x+3)(x-3))#

#= ((2x+5))/((x-3))#